Evaluation of Seawater Intrusion and Groundwater Quality in the Coastal Aquifers in Srikakulam District, A.P., India Using Electrical Conductivity Property - K, Sai Kiran; K, Nooka Ratnam; G, Swathi; T, Sankara Rao; B, Ramakrishna; G, Shiva Prasad; K, satyanarayananaidu (International Journal of Membrane Science and Technology, 2023)
Seawater intrusion into coastal aquifers has emerged as a significant environmental threat that imperils water resources, especially groundwater resources, ecosystems, and human health. It is widely acknowledged that water plays an indispensable role in the maintenance of life. Groundwater is an important source, particularly in arid and semi-arid regions where surface water and precipitation are limited. Management of a safe and renewable supply of groundwater for drinking and agricultural purposes is one of the crucial aspects of sustainable development for any Nation. But the groundwater quality faces threats from urbanization, agricultural practices, industrial activities, climate changes, and groundwater parameters such as pH, Electrical Conductivity (EC), Total Dissolve Solids (TDS), fluoride, chloride, calcium, sulfate, and iron. In the present study, 13 coastal mandals viz., Ranastalam, Laveru, Etcherla, Srikakulam, Gara, Polaki, Santhabommali, Vajrapukotturu, Mandasa, Sompeta, Kanchili, Kaviti and Ichapuram in Srikakulam district, A.P., India, have been considered. The quality of the groundwater in these mandals has been assessed based on seawater intrusion into the coastal aquifers considering the EC and TDS parameters which help identifying seawater intrusion. Among all the 13 coastal mandals, the Gara, Polaki, Sompeta, Santabommali, and Ichapuram mandala are much influenced by seawater intrusion. The geology, geomorphology, climate, rainfall, and soil types of the study areas have been discussed. 61 water samples from bore wells of the 13 mandals have been collected for the present study. All the water samples were analyzed to determine the groundwater quality based on the EC and TDS of the water.